Existentiell ångest och den tragiska treklövern i ljuset av ungas psykiska ohälsa - Nilsson, Håkan (Socialmedicinsk tidskrift, 2023)
The purpose of this article is, through a close reading of Paul Tillich’s book The Courage to Be and Viktor Frankl’s book Life must have a meaning, to illuminate similarities and differences in the view of existential anxiety as a predicament in the individual’s search for meaning. The article discusses how anxiety is channeled through fate and death, guilt and condemnation and emptiness and meaninglessness. Frankl’s tragic triad: pain, guilt and death running like a red line through these anxiety impulses. From a contemporary context, Tillich and Frankl’s thoughts raise questions about how we can approach young people’s mental illness.